Case report: Post-COVID new-onset neurocognitive decline with bilateral mesial-temporal hypometabolism in two previously healthy sisters - Cocciolillo, Fabrizio; Chieffo, Daniela Pia Rosaria; Giordano, Alessandro; Arcangeli, Valentina; Lazzareschi, Ilaria; Morello, Rosa; Zampino, Giuseppe; Valentini, Piero; Buonsenso, Danilo (Frontiers in Pediatrics, 2023)
Background: Long Covid is increasingly recognized in adults and children, however it is still poorly characterized on a clinical and diagnostic perspective, particularly in the younger populations. Case presentation: we describe the story of two sisters – with high social and academic performance before their SARS-CoV-2 infection – which reported severe neurocognitive problems, initially classified as psychologic pandemic distress, and eventually found to have significant brain hypometabolism. Conclusions: we provided a detailed clinical presentation of neurocognitive symptoms in two sisters with Long Covid associated to brain hypometabolism documented in both sisters. We believe that the evidence of objective findings in these children provide further support to the hypothesis that organic events are the cause of persisting symptoms in a cohort of children after SARS-CoV-2 infection. Such findings highlight the importance of discovering diagnostics and therapeutics.